2011
DOI: 10.1016/j.molcel.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

RNase H and Multiple RNA Biogenesis Factors Cooperate to Prevent RNA:DNA Hybrids from Generating Genome Instability

Abstract: Genome instability, a hallmark of cancer progression, is thought to arise through DNA double strand breaks (DSBs). Studies in yeast and mammalian cells have shown that DSBs and instability can occur through RNA-DNA hybrids generated by defects in RNA elongation and splicing. We report that in yeast hybrids naturally form at many loci in wild-type cells, likely due to transcriptional errors, but are removed by two evolutionarily conserved RNase H enzymes. Mutants defective in transcriptional repression, RNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
398
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(426 citation statements)
references
References 44 publications
(53 reference statements)
19
398
0
Order By: Relevance
“…R-loops form normally in many circumstances, including Ig class switch recombination and transcription termination, and are actively resolved by RNA:DNA helicases and RNase H1 and H2 (39,56). Persistent R-loops can become deleterious, however.…”
Section: Discussionmentioning
confidence: 99%
“…R-loops form normally in many circumstances, including Ig class switch recombination and transcription termination, and are actively resolved by RNA:DNA helicases and RNase H1 and H2 (39,56). Persistent R-loops can become deleterious, however.…”
Section: Discussionmentioning
confidence: 99%
“…Third, TERRA is associated with telomeres. If TERRA and telomeric DNA form R-loops, which are characterized by RNA-DNA hybrids and the displacement of single-stranded DNA, they may need to be resolved by helicases in order to avoid formation of double-stranded DNA breaks (Huertas and Aguilera 2003;Chawla et al 2011;Wahba et al 2011). …”
Section: Telomerasementioning
confidence: 99%
“…The failure in these studies to reveal a prominent role for RNase H1 in protecting against hybrid-mediated chromosome instability also was surprising. Previous studies had shown that RNase H1, when constitutively overexpressed, can suppress genome-wide hybrid formation and hybrid-mediated genome instability induced by mutations in the RNA biogenesis machinery (3,6,7). These results suggested that RNase H1 had the ability to remove many hybrids within the cell but could do so only under artificial conditions of constitutive overexpression, not addressing the roles that RNase H1 and H2 play in physiological conditions.…”
mentioning
confidence: 94%
“…Studies of the inactivation of RNase H1 in yeast have shown little effect on chromosome instability (3,4), whereas inactivation of RNase H2 has been shown to increase chromosome instability (4,5). However, results from the Conover study (5) suggested that the elevated instability in the RNase H2-deficient cells is caused by elevated misincorporation of ribonucleotides rather than by the failure to remove hybrids.…”
mentioning
confidence: 99%